2011
DOI: 10.1164/rccm.201105-0802oc
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Dysfunction Causes Sustained Inflammation in Chronic Obstructive Pulmonary Disease

Abstract: Telomere dysfunction and premature P-EC senescence are major processes perpetuating lung inflammation in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
156
2
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(179 citation statements)
references
References 33 publications
14
156
2
7
Order By: Relevance
“…With respect to COPD, this might be consistent with the observation that females appear to be more susceptible to COPD than males [34] but the causality certainly needs to be proved. Whereas our findings for asthma are novel, the results for COPD are in line with previous findings in case-control [14][15][16][17] and population-based studies [18]. This suggests that, as already shown for other chronic diseases [1,3,35], accelerated ageing may contribute to the pathogenesis of asthma and COPD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…With respect to COPD, this might be consistent with the observation that females appear to be more susceptible to COPD than males [34] but the causality certainly needs to be proved. Whereas our findings for asthma are novel, the results for COPD are in line with previous findings in case-control [14][15][16][17] and population-based studies [18]. This suggests that, as already shown for other chronic diseases [1,3,35], accelerated ageing may contribute to the pathogenesis of asthma and COPD.…”
Section: Discussionsupporting
confidence: 92%
“…Recent data suggest that shorter telomere length is associated with an increased risk of total and cancer mortality in COPD patients [13]. Shortened telomeres were found in pulmonary vascular endothelial cells, alveolar epithelial cells and circulating leukocytes of COPD patients [14][15][16][17][18], supporting the notion of accelerated ageing in COPD. RODE et al [18] reported multivariable-adjusted odds ratios of 1.15 (95% CI 1.06-1.25) for shortest versus longest telomere quartiles for COPD.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…These stimuli can act through two main different pathways: p53‐p21 and p16‐retinoblastoma protein (pRb), respectively (Campisi, 2005). In the lung, cell senescence leads to a decreased regenerative capacity and an increased cytokine production by structural cells (epithelium, fibroblasts) through a senescence‐associated secretome (Amsellem et al, 2011; Dagouassat et al, 2013; Noureddine et al, 2011; Tsuji, Aoshiba, & Nagai, 2010). However, other mechanisms, including mitochondrial dysfunction and defective mitophagy, may also contribute to ROS‐mediated senescence in COPD (Lerner, Sundar, & Rahman, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[39] Telomere dysfunction is one of the major processes perpetuating pulmonary inflammation in COPD. [40] COPD patients were reported to have shorter telomeres in leukocytes, out of 46,396 individuals from the Danish general population. Rode et al found that shortened telomere length was associated with higher risk of COPD, though the association was markedly attenuated after age and multivariable adjustment.…”
Section: Loss Of Telomeresmentioning
confidence: 99%